Design and development of smart surgical assistant technologies : a case study for translational sciences /: a case study for translational sciences. (2022) - Kim, Jeff J. H; Um, Richard; Iyer, Rajiv R; Theodore, Nicholas; Manbachi, Amir
No abstract available